Antibacterial Activity of Freshwater Sponge Oncosclera asiatica Against Escherichia coli and Staphylococcus aureus - Wulandari, Dyah; Dewantoro, Giwang; Lunggani, Arina Tri; Suprihadi, Agung; Riani, Catur; Setiawan, Edwin; Farikha, Siti Lutfiatul; Budiharjo, Anto (Bioma : Berkala Ilmiah Biologi, 2022)
Freshwater sponges are animals from the Porifera phylum that live in freshwater. The sponge used is Oncosclera asiatica was taken from Kali Porong, East Java. Seventeen isolates of bacteria have been obtained from isolation. Antibacterial potential testing was performed by paper disc inhibition assay using Escherichia coli and Staphylococcus aureus as pathogenic bacteria and amoxicillin as a positive control. The antibacterial activity test showed that four isolates have the potential activity. The isolates with the highest inhibition zones were identified using a 16S rRNA.The results of BLAST showed isolate number 2 was Pseudomonas moraviensis with 99.51% similarity. The phylogenetic tree analysis was build using the MEGA X program. The results of the phylogenetic tree analysis showed that P.moraviensis had a bootstrap value of 100% with a  genetic distance value of 0.001. P. moraviensis isolates screened for the presence of Non-Ribosomal Peptide Synthetase (NRPS) gene by A2gamF and A3gamR primers. The amplification result from NRPS gene showed positive meaning that P.moraviensis genome contained NRPS gene.